Assessment of bending strength of afara glued laminated timber using polyurethane (PUR) adhesive - Sanni, Pamilerin; Ekundayo, Oluwarotimi (Penerbit Universiti Kebangsaan Malaysia, 2022)
Timber has long been a popular building material, with benefits such as low energy consumption and the ability to create an in-built atmosphere that helps to mitigate the effects of global warming. Afara (Terminalia Superba) is a well-known timber species with high demand in Nigeria. The objective of this paper is to assess the physical and mechanical properties of Afara (Terminalia Superba) wood, as well as the flexural strength in flatwise bending of its glued laminated timber beam using polyurethane (PUR) adhesive, to determine its viability for structural construction. The research specimens were made using MS758:2001, EN408, and ASTM D198:2013 standards for the physical and mechanical properties tests. By MS758:2001, a shear test for glue line integrity was conducted to assess the bond performance of the glulam. In the laboratory, bending tests were performed on five glulam beams and five solid beams. Glulam beams were glued together with polyurethane (PUR) adhesive. The bending strength of solid wood was higher than that of glue-laminated wood. Solid Afara (Terminalia Superba) beams have a bending strength of 40.09 N/mm2, whereas glued laminated timber has a bending strength of 19.18 N/mm2. The preliminary investigation of the timber under BS 5268 (structural use of timber) revealed that glue-laminated beams can be used as structural members in a flatwise orientation, despite their strength being lesser than that of solid beams. Also, the polyurethane adhesive strength has an inverse relationship with the moisture content of the specimens at room temperature.